Kapcsolatok és jövedelem, Magyarország 1986-1987 - Böröcz, József; Southworth, Caleb (Szociológiai Szemle, 2024)
While social network assets have been widely studied — albeit quite inadequately theorized — as mechanisms for social achievement in the capitalist context, they have remained unduly outside of the focus of empirical work under socialism. In the second of a series of studies utilizing „Milieux”, the 1986-87 dataset on social networks and stratification in Hungary, this study addresses that weakness in the literature and tests the usefulness of social network resources in income attainment models. It offers a conceptual and measurement-oriented critique of the conventional characterization of ties as either „weak” or „strong”, and suggests that the formal-informal distinction is more useful as a basic taxonomy of social network assets. We argue that formal and informal ties criss-cross both the state and non-state sectors of the Hungarian economy — hence we measure them separately in all combinations of economic sectors. OLS hierarchical regression models show that social network resources contributed quite measurably to income inequality under late state socialism in Hungary. We also find that formal and informal network ties have independent and unequal returns; they are hence to be treated as qualitatively different types of ties rather than poles or distinct sections in a one-dimensional spectrum.